Race and Sociocultural Inclusion in Science Communication Innovation, Decolonisation, and Transformation - Rasekoala, Elizabeth (Bristol University Press, 2023)
Conversations around diversity, equity, and inclusion in science communication are in danger of generating much concern without effecting change and systematic transformations. This radical volume addresses these circular discourses and reveals the gaps in the field. Putting the spotlight on the marginalised voices of so-called 'racialised minorities', and those from Global South regions, it interrogates the global footprint of the science communication enterprise. Moving beyond tokenistic and extractive approaches, this book creates a space for academics and practitioners to challenge issues around race and sociocultural inclusion, providing mutual learning, paradigm-shifting perspectives, and innovative ways forward for the science communication advancement agenda. Chapter 12 is available Open Access under CC-BY-NC-ND licence.